Mapping the evidence on the impact of heat stress on exercise and work performance in females: a scoping review - Gilworth, Rachel E.; Skinner, Bethany D.; Hodgkiss, Daniel D.; Lucas, Samuel J. E.; Lucas, Rebekah A. I. (Frontiers in Physiology, 2025)
Increasing numbers of females are performing in increasingly hot environments. This scoping review aimed to 1) collate evidence on the effects of environmental heat stress on aerobic exercise performance and work productivity in females specifically, and 2) explore sex differences in the existing literature. A systematic search across four databases (PubMed, MEDLINE, Web of Science and SPORTDiscus) was developed based on MeSH terms and keywords, with all permutations relating to ‘FEMALE’, ‘WOMAN’, ‘HEAT’ AND ‘PERFORMANCE’. Identified articles were screened against pre-defined inclusion criteria related to age (16–60 years), environmental heat stress (≥23°C), and physical activity duration (≥5 min). We identified 35,696 articles, of which 41 met the inclusion criteria. Of the included studies, 19 reported female-specific comparisons, two of which also investigated sex differences. Four studies investigated sex differences alone, while 18 studies included females within the participant cohort. Thirty-eight of the included studies assessed athletic performance and three studies examined occupational performance (i.e., work output/productivity) in females. Existing data on the effect of heat stress on performance was predominantly from pre-menopausal cohorts (mean age 29 years, range 20–46 years), with no studies investigating peri- or post-menopausal cohorts. We uncovered limited research investigating the effect of menstrual cycle phase (six studies) or hormonal contraceptive use (two studies) on performance in the heat. Thirteen included studies examined interventions pre or during performance test(s), with four studies showing their interventions attenuated heat stress performance impairments in female cohorts. We highlight notable gaps in the literature regarding female performance in the heat; specifically, the influence of peri-post menopause, heat stress interventions for females, and impacts on females in the occupational sector. We recommend that researchers undertaking exercise and thermal physiological research aim for gender balance where possible and adhere to guidelines when designing and reporting research that encompasses females. Addressing these research gaps would provide workers, athletes, and practitioners with a better understanding of how to protect females and enhance their physical performance in the heat, across different stages of life, amidst a changing climate.